Method for preparing sodium ion hard carbon from lignin modified phenolic resin doped with S in situ

Through the preparation method of in-situ S-doped lignin-modified phenolic resin, the problem of poor sodium storage performance of existing phenolic resin hard carbon materials was solved, and sodium ion hard carbon materials with improved structure were prepared, which significantly improved its storage Sodium properties and electrochemical properties.

CN119390047AActive Publication Date: 2025-02-07INST OF CHEM IND OF FOREST PROD CHINESE ACAD OF FORESTRY
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411359753.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-02-07
Estimated Expiration
2044-09-27

AI Technical Summary

Technical Problem

The existing phenolic resin hard carbon materials have low oxygen content, low layer spacing, and small number of microcrystals, resulting in poor sodium storage performance and difficult to meet the application needs of sodium ion batteries.

Method used

By the preparation method of in-situ S-doped lignin modified phenolic resin, the sodium ion hard carbon material with improved structure is prepared by using the prepolymer of sulfonated lignin and phenolic resin, followed by carbonization and high-temperature refining.

Benefits of technology

It improves the layer spacing, number of ultra-micropores and specific surface area of ​​sodium ion hard carbon materials, significantly improves its sodium storage performance and electrochemical performance, and is suitable for sodium ion battery negative electrode materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119390047A_ABST
    Figure CN119390047A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing sodium ion hard carbon from lignin modified phenolic resin doped with S in situ, and belongs to the technical field of lignin modification, phenolic resin synthesis and sodium ion negative electrode hard carbon material preparation. Anhydrous sodium sulfite is added through a hydrothermal method, lignin is doped with an S element in situ and then is copolymerized with a phenolic prepolymer, lignin sulfonate phenolic resin is obtained, and lignin sulfonate modified phenolic resin-based hard carbon is prepared through curing and high-temperature carbonization treatment. By in-situ doping of the S element, the conductivity of the material can be improved, the specific surface area of the material is affected, the electrochemical performance of the material is improved, and oriented regulation and control of the sulfonated lignophenolic resin structure are realized. The problem of poor storage performance caused by small spacing, poor conductivity and large specific surface area of lignin phenolic resin hard carbon layers is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lignin modification, phenolic resin synthesis and preparation of sodium ion negative electrode hard carbon materials, and in particular relates to a method for preparing sodium ion hard carbon by in-situ doped S-doped lignin modified phenolic resin. Background Art

[0002] The advantages of phenolic resin hard carbon include good application prospects, fast market growth, and good application in the field of sodium batteries and lithium battery negative electrode doping. Phenolic resin hard carbon is expected to be used first because of its relatively easy production process. In addition, the demand for hard carbon materials is expected to increase from 2,000 tons / year in 2022 to 105,000 tons / year in 2025, showing its rapid growth potential in the market. In terms of market space, it is expected that the market space for hard carbon materials will reach 6.3 billion yuan by 2025. In summary, phenolic resin hard carbon, as a potential negative electrode material, has broad application prospects and rapid market growth expectations, but it also faces technical difficulties and performance challenges. Mainly because the oxygen content of the material is low, the interlayer spacing of the prepared hard carbon material is low, and the number of crystallites is small. Therefore, it is necessary to further improve its performance and application scope through technological innovation and material optimization.

[0003] The advantages of biomass-modified phenolic resins are mainly reflected in improving mechanical properties, reducing free formaldehyde release, improving thermal stability, enhancing wear resistance and impact resistance, and improving dimensional stability, making it have broad application prospects in many fields. Lignin and its derivatives are representative substances of biological raw materials. They have rich oxygen-containing functional groups and can react with phenolic resins under specific conditions to improve the chemical properties of phenolic resins.

[0004] The high S content of hard carbon materials can increase the diffusion rate of Na+, lead to the expansion of interlayer spacing, enhance porosity and form defects, which is beneficial to the improvement of sodium storage performance. Since lignin itself contains S elements, it is possible to consider in-situ doping S on the lignin molecules, and then oxidize them to expose their reactive sites and react with phenolic resin prepolymers to achieve the purpose of modifying the phenolic resin structure, thereby changing the chemical structure and sodium storage performance of lignin phenolic resin hard carbon sodium ion negative electrode materials, providing advantages for their application in sodium ion batteries and other fields. Summary of the invention

[0005] The first purpose of the present invention is to propose a method for preparing sodium ion hard carbon by in-situ doped S lignin modified phenolic resin, wherein the S content of lignin is regulated by in-situ doping technology, and then a sulfonation pretreatment is performed to increase the sulfur-containing groups on the lignin. Subsequent oxidation exposes the sulfur-containing groups and oxygen-containing functional groups on the sulfonated lignin, which is beneficial to the subsequent modification of the phenolic resin by the sulfonated lignin, thereby realizing the controllable regulation of the molecular structure of the phenolic resin by the in-situ doped S lignin.

[0006] The second purpose of the present invention is to provide a sodium ion hard carbon prepared by in-situ doped S lignin modified phenolic resin, which forms a thinner and more uniform SEI film during the sodium storage process due to the increase in the carbon microcrystalline layer spacing, the increase in the number of ultra-micropores, and the decrease in specific surface area.

[0007] The third object of the present invention is to disclose the application of a sulfonated lignin phenolic resin-based hard carbon in a negative electrode material for a sodium ion battery, which exhibits excellent first efficiency and reversible capacity.

[0008] In order to solve the above problems, the technical solution adopted by the present invention is as follows:

[0009] A method for preparing sodium ion hard carbon from a lignin-modified phenolic resin in situ doped with S comprises the following steps: firstly, sodium lignin sulfonate and anhydrous sodium sulfite are hydrothermally prepared to obtain sulfonated lignin; then, the sulfonated lignin is oxidized and polycondensed with a phenolic resin prepolymer to obtain a sulfonated lignin phenolic resin; and then, the sulfonated lignin phenolic resin is cured and carbonized to obtain a sulfonated lignin-modified phenolic resin-based hard carbon.

[0010] Furthermore, the mass ratio of the sodium lignin sulfonate to anhydrous sodium sulfite is 1:2 to 2:1.

[0011] Furthermore, the mass ratio of the sodium lignin sulfonate to anhydrous sodium sulfite is 1:1.225.

[0012] Furthermore, the preparation method of sulfonated lignin is as follows: sodium lignin sulfonate and anhydrous sodium sulfite are dissolved in a NaOH aqueous solution, stirred for 1 hour, and then heated to react to prepare sulfonated lignin, and after separation, water washing, drying, and grinding, sulfonated lignin powder is obtained.

[0013] Furthermore, the temperature of the heating reaction is 100-200°C.

[0014] Furthermore, the temperature of the heating reaction is 160°C.

[0015] Furthermore, the heating reaction time is 2-6h.

[0016] Furthermore, the heating reaction time is 4 hours.

[0017] Furthermore, the sulfonated lignin phenolic resin-based hard carbon prepared by any of the above methods.

[0018] Furthermore, the sulfonated lignin phenolic resin-based hard carbon is used in the negative electrode material of sodium ion battery.

[0019] Compared with the prior art, the advantages of the present invention are as follows:

[0020] 1) The present invention utilizes the sulfonation effect of in-situ doping with S to expose more oxygen functional groups and sulfur-containing groups on lignin by increasing the sulfur-containing groups of lignin and subsequent oxidation, thereby achieving directional regulation of the molecular structure of phenolic resin by sulfonated lignin, solving the problems of regulation of S and O elements on the molecular structure of lignin, qualitative increase of sulfur-containing and oxygen-containing groups on phenolic resin, and the interlayer spacing and pore structure of phenolic resin and hard carbon before modification being unfavorable for improving storage performance.

[0021] 2) The present invention utilizes sulfonated lignin to pre-treat modified phenolic resin raw materials to prepare hard carbon. Compared with the traditional phenolic resin-based hard carbon preparation method, the hard carbon has excellent sodium storage performance and low toxicity. By modifying the molecular structure of the phenolic resin hard carbon precursor with sulfonated lignin, the interlayer spacing of the sulfonated lignin phenolic resin-based hard carbon is increased, the specific surface area is reduced, and the number of ultra-micropores is increased, which is beneficial to improving the electrochemical performance of the negative electrode material of the sodium ion battery.

[0022] 3) The preparation method disclosed in the present invention is simple to operate, has low energy consumption, and has low requirements on equipment. It also has reference significance for other types of biomass-modified phenolic resins and their preparation of hard carbon materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 XRD diagrams of different optimized conditions for sulfonated lignin reaction in Examples 2 to 5 of the present invention;

[0024] Figure 2 XRD diagrams of different optimized conditions for the sulfonated lignin reaction in Examples 3 and 8 to 10 of the present invention;

[0025] Figure 3 These are XRD diagrams of different optimized conditions for the sulfonated lignin reactions in Examples 3 and 11 to 13 of the present invention. DETAILED DESCRIPTION

[0026] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with specific embodiments.

[0027] Unless otherwise specified in the following examples, the technical means used are conventional means known to those skilled in the art. If no specific conditions are specified in the examples, the conditions are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0028] The test method adopted by the present invention is as follows:

[0029] 1. Molecular structure property test

[0030] X-ray diffraction (XRD) was used to analyze the structure of hard carbon using Cu Kα rays at a scanning rate of 5° / min. The molecular weight of the sample was tested using Waters 1525 & Agilent PL-GPC 220 (GPC), with water and chloroform as solvents.

[0031] 2. Battery performance test (discharge specific capacity (mAh g -1 ) and first effect)

[0032] 2.1 Battery Production

[0033] Preparation of electrode: Hard carbon material, conductive agent (super-P) and binder (PVDF) were mixed in a mass ratio of 7:1:1, and NMP was used as a dispersant to prepare a slurry, which was coated on copper foil and dried in a forced air drying oven at 80°C for 12 hours. The dried electrode sheet was punched into a circular electrode sheet with a diameter of 15 mm for later use.

[0034] Assembly of button half-cell: The battery was assembled in an argon glove box with a moisture and oxygen content of less than 0.01 ppm, using a CR2032 battery case and 1 mol / L NaPF electrolyte. 6 (The solvent is a mixture of ethylene carbonate: dimethyl carbonate: ethyl methyl carbonate in a volume ratio of 1:1:1), the metal sodium sheet is used as both the counter electrode and the reference electrode, and the diaphragm is a GF / D glass fiber diaphragm. The battery is assembled from the bottom up in the order of positive electrode shell, electrode sheet, diaphragm, sodium sheet, gasket, shrapnel and negative electrode shell.

[0035] 2.2 Performance Testing

[0036] The constant current charge and discharge test (GCD) was performed on the CT-4008Tn battery testing system.

[0037] Comparative Example

[0038] 5g of lignin was oxidized and then polycondensed with a phenolic resin prepolymer to prepare a sulfonated lignin-modified phenolic resin, which was finally carbonized and refined at high temperature to obtain a sulfonated lignin-modified phenolic resin hard carbon.

[0039] Example 1

[0040] A method for preparing sodium ion hard carbon by in-situ doping S-doped lignin-modified phenolic resin, comprising the following steps:

[0041] (1) First, 5 g of sodium lignin sulfonate and 2.5 g of anhydrous sodium sulfite were dissolved in 30 mL of 3 mol / L NaOH aqueous solution, stirred for 1 h, and transferred to a high-pressure reactor at 160 ° C for reaction for 3 h to prepare a sulfonated lignin mixed solution;

[0042] (2) separating, washing, drying and grinding the sulfonated lignin mixed solution obtained in step (1) to obtain sulfonated lignin powder;

[0043] (3) Take 5 g of the sulfonated lignin powder obtained in step (2), first oxidize it, then condense it with a phenolic resin prepolymer to prepare a sulfonated lignin-modified phenolic resin, and finally carbonize and refine it at high temperature to obtain a sulfonated lignin-modified phenolic resin hard carbon.

[0044] Example 2

[0045] A method for preparing sodium ion hard carbon by in-situ doping S-doped lignin-modified phenolic resin, comprising the following steps:

[0046] (1) First, 5 g of sodium lignin sulfonate and 5 g of anhydrous sodium sulfite were dissolved in 30 mL of 3 mol / L NaOH aqueous solution, stirred for 1 h, and transferred to a high-pressure reactor at 160 ° C for reaction for 3 h to prepare a sulfonated lignin mixed solution;

[0047] (2) separating, washing, drying and grinding the sulfonated lignin mixed solution obtained in step (1) to obtain sulfonated lignin powder;

[0048] (3) Take 5 g of the sulfonated lignin powder obtained in step (2), first oxidize it, then condense it with a phenolic resin prepolymer to prepare a sulfonated lignin-modified phenolic resin, and finally carbonize and refine it at high temperature to obtain a sulfonated lignin-modified phenolic resin hard carbon.

[0049] Example 3

[0050] A method for preparing sodium ion hard carbon by in-situ doping S-doped lignin-modified phenolic resin, comprising the following steps:

[0051] (1) First, 5 g of sodium lignin sulfonate and 6.125 g of anhydrous sodium sulfite were dissolved in 30 mL of 3 mol / L NaOH aqueous solution, stirred for 1 h, and transferred to a high-pressure reactor at 160 ° C for reaction for 3 h to prepare a sulfonated lignin mixed solution;

[0052] (2) separating, washing, drying and grinding the sulfonated lignin mixed solution obtained in step (1) to obtain sulfonated lignin powder;

[0053] (3) Take 5 g of the sulfonated lignin powder obtained in step (2), first oxidize it, then condense it with a phenolic resin prepolymer to prepare a sulfonated lignin-modified phenolic resin, and finally carbonize and refine it at high temperature to obtain a sulfonated lignin-modified phenolic resin hard carbon.

[0054] Example 4

[0055] A method for preparing sodium ion hard carbon by in-situ doping S-doped lignin-modified phenolic resin, comprising the following steps:

[0056] (1) First, 5 g of sodium lignin sulfonate and 7.5 g of anhydrous sodium sulfite were dissolved in 30 mL of 3 mol / L NaOH aqueous solution, stirred for 1 h, and transferred to a high-pressure reactor at 160 ° C for reaction for 3 h to prepare a sulfonated lignin mixed solution;

[0057] (2) separating, washing, drying and grinding the sulfonated lignin mixed solution obtained in step (1) to obtain sulfonated lignin powder;

[0058] (3) Take 5 g of the sulfonated lignin powder obtained in step (2), first oxidize it, then condense it with a phenolic resin prepolymer to prepare a sulfonated lignin-modified phenolic resin, and finally carbonize and refine it at high temperature to obtain a sulfonated lignin-modified phenolic resin hard carbon.

[0059] Example 5

[0060] A method for preparing sodium ion hard carbon by in-situ doping S-doped lignin-modified phenolic resin, comprising the following steps:

[0061] (1) First, 5 g of sodium lignin sulfonate and 8.125 g of anhydrous sodium sulfite were dissolved in 30 mL of 3 mol / L NaOH aqueous solution, stirred for 1 h, and transferred to a high-pressure reactor at 160 ° C for reaction for 3 h to prepare a sulfonated lignin mixed solution;

[0062] (2) separating, washing, drying and grinding the sulfonated lignin mixed solution obtained in step (1) to obtain sulfonated lignin powder;

[0063] (3) Take 5 g of the sulfonated lignin powder obtained in step (2), first oxidize it, then condense it with a phenolic resin prepolymer to prepare a sulfonated lignin-modified phenolic resin, and finally carbonize and refine it at high temperature to obtain a sulfonated lignin-modified phenolic resin hard carbon.

[0064] Example 6

[0065] A method for preparing sodium ion hard carbon by in-situ doping S-doped lignin-modified phenolic resin, comprising the following steps:

[0066] (1) First, 5 g of sodium lignin sulfonate and 10 g of anhydrous sodium sulfite were dissolved in 30 mL of 3 mol / L NaOH aqueous solution, stirred for 1 h, and transferred to a high-pressure reactor at 160 ° C for reaction for 3 h to prepare a sulfonated lignin mixed solution;

[0067] (2) separating, washing, drying and grinding the sulfonated lignin mixed solution obtained in step (1) to obtain sulfonated lignin powder;

[0068] (3) Take 5 g of the sulfonated lignin powder obtained in step (2), first oxidize it, then condense it with a phenolic resin prepolymer to prepare a sulfonated lignin-modified phenolic resin, and finally carbonize and refine it at high temperature to obtain a sulfonated lignin-modified phenolic resin hard carbon.

[0069] The samples prepared in the above Examples 1 to 6 and the comparative example were tested for molecular structure properties and battery performance, and the test results are shown in Table 1 below.

[0070] Table 1 Comparison of sodium storage performance of sulfonated lignin modified phenolic resin hard carbon with different anhydrous sodium sulfite in Examples 1 to 6 and Comparative Examples

[0071]

[0072] From the comparison of the data in Table 1, it can be seen that when the amount of anhydrous sodium sulfite water added is 6.125g, the discharge specific capacity is the highest.

[0073] Example 7

[0074] A method for preparing sodium ion hard carbon by in-situ doping S-doped lignin-modified phenolic resin, comprising the following steps:

[0075] (1) First, 5 g of sodium lignin sulfonate and 6.125 g of anhydrous sodium sulfite were dissolved in 30 mL of 3 mol / L NaOH aqueous solution, stirred for 1 h, and transferred to a high-pressure reactor at 120 ° C for reaction for 3 h to prepare a sulfonated lignin mixed solution;

[0076] (2) separating, washing, drying and grinding the sulfonated lignin mixed solution obtained in step (1) to obtain sulfonated lignin powder;

[0077] (3) Take 5 g of the sulfonated lignin powder obtained in step (2), first oxidize it, then condense it with a phenolic resin prepolymer to prepare a sulfonated lignin-modified phenolic resin, and finally carbonize and refine it at high temperature to obtain a sulfonated lignin-modified phenolic resin hard carbon.

[0078] Example 8

[0079] A method for preparing sodium ion hard carbon by in-situ doping S-doped lignin-modified phenolic resin, comprising the following steps:

[0080] (1) First, 5 g of sodium lignin sulfonate and 6.125 g of anhydrous sodium sulfite were dissolved in 30 mL of 3 mol / L NaOH aqueous solution, stirred for 1 h, and transferred to a high-pressure reactor at 140 ° C for reaction for 3 h to prepare a sulfonated lignin mixed solution;

[0081] (2) separating, washing, drying and grinding the sulfonated lignin mixed solution obtained in step (1) to obtain sulfonated lignin powder;

[0082] (3) Take 5 g of the sulfonated lignin powder obtained in step (2), first oxidize it, then condense it with a phenolic resin prepolymer to prepare a sulfonated lignin-modified phenolic resin, and finally carbonize and refine it at high temperature to obtain a sulfonated lignin-modified phenolic resin hard carbon.

[0083] Example 9

[0084] A method for preparing sodium ion hard carbon by in-situ doping S-doped lignin-modified phenolic resin, comprising the following steps:

[0085] (1) First, 5 g of sodium lignin sulfonate and 6.125 g of anhydrous sodium sulfite were dissolved in 30 mL of 3 mol / L NaOH aqueous solution, stirred for 1 h, and transferred to a high-pressure reactor at 180 ° C for reaction for 3 h to prepare a sulfonated lignin mixed solution;

[0086] (2) separating, washing, drying and grinding the sulfonated lignin mixed solution obtained in step (1) to obtain sulfonated lignin powder;

[0087] (3) Take 5 g of the sulfonated lignin powder obtained in step (2), first oxidize it, then condense it with a phenolic resin prepolymer to prepare a sulfonated lignin-modified phenolic resin, and finally carbonize and refine it at high temperature to obtain a sulfonated lignin-modified phenolic resin hard carbon.

[0088] Example 10

[0089] A method for preparing sodium ion hard carbon by in-situ doping S-doped lignin-modified phenolic resin, comprising the following steps:

[0090] (1) First, 5 g of sodium lignin sulfonate and 6.125 g of anhydrous sodium sulfite were dissolved in 30 mL of 3 mol / L NaOH aqueous solution, stirred for 1 h, and transferred to a high-pressure reactor at 200 ° C for reaction for 3 h to prepare a sulfonated lignin mixed solution;

[0091] (2) separating, washing, drying and grinding the sulfonated lignin mixed solution obtained in step (1) to obtain sulfonated lignin powder;

[0092] (3) Take 5 g of the sulfonated lignin powder obtained in step (2), first oxidize it, then condense it with a phenolic resin prepolymer to prepare a sulfonated lignin-modified phenolic resin, and finally carbonize and refine it at high temperature to obtain a sulfonated lignin-modified phenolic resin hard carbon.

[0093] The molecular structure properties and battery performance of the samples prepared in the above-mentioned Example 3, Examples 7 to 10 and Comparative Examples were tested, and the test results are shown in Table 2 below.

[0094] Table 2 Comparison of sodium storage performance of sulfonated lignin modified phenolic resin hard carbon at different sulfonation reaction temperatures in Example 3, Examples 7 to 10 and Comparative Examples

[0095]

[0096] It can be seen from the data in the above table that when the reaction temperature of sulfonated lignin is 160°C, the discharge specific capacity is the highest.

[0097] Embodiment 11

[0098] A method for preparing sodium ion hard carbon by in-situ doping S-doped lignin-modified phenolic resin, comprising the following steps:

[0099] (1) First, 5 g of sodium lignin sulfonate and 6.125 g of anhydrous sodium sulfite were dissolved in 30 mL of 3 mol / L NaOH aqueous solution, stirred for 1 h, and transferred to a high-pressure reactor at 160 ° C for reaction for 2 h to prepare a sulfonated lignin mixed solution;

[0100] (2) separating, washing, drying and grinding the sulfonated lignin mixed solution obtained in step (1) to obtain sulfonated lignin powder;

[0101] (3) Take 5 g of the sulfonated lignin powder obtained in step (2), first oxidize it, then condense it with a phenolic resin prepolymer to prepare a sulfonated lignin-modified phenolic resin, and finally carbonize and refine it at high temperature to obtain a sulfonated lignin-modified phenolic resin hard carbon.

[0102] Example 12

[0103] A method for preparing sodium ion hard carbon by in-situ doping S-doped lignin-modified phenolic resin, comprising the following steps:

[0104] (1) First, 5 g of sodium lignin sulfonate and 6.125 g of anhydrous sodium sulfite were dissolved in 30 mL of 3 mol / L NaOH aqueous solution, stirred for 1 h, and transferred to a high-pressure reactor at 160 ° C for reaction for 4 h to prepare a sulfonated lignin mixed solution;

[0105] (2) separating, washing, drying and grinding the sulfonated lignin mixed solution obtained in step (1) to obtain sulfonated lignin powder;

[0106] (3) Take 5 g of the sulfonated lignin powder obtained in step (2), first oxidize it, then condense it with a phenolic resin prepolymer to prepare a sulfonated lignin-modified phenolic resin, and finally carbonize and refine it at high temperature to obtain a sulfonated lignin-modified phenolic resin hard carbon.

[0107] Embodiment 13

[0108] A method for preparing sodium ion hard carbon by in-situ doping S-doped lignin-modified phenolic resin, comprising the following steps:

[0109] (1) First, 5 g of sodium lignin sulfonate and 6.125 g of anhydrous sodium sulfite were dissolved in 30 mL of 3 mol / L NaOH aqueous solution, stirred for 1 h, and transferred to a high-pressure reactor at 160 ° C for reaction for 5 h to prepare a sulfonated lignin mixed solution;

[0110] (2) separating, washing, drying and grinding the sulfonated lignin mixed solution obtained in step (1) to obtain sulfonated lignin powder;

[0111] (3) Take 5 g of the sulfonated lignin powder obtained in step (2), first oxidize it, then condense it with a phenolic resin prepolymer to prepare a sulfonated lignin-modified phenolic resin, and finally carbonize and refine it at high temperature to obtain a sulfonated lignin-modified phenolic resin hard carbon.

[0112] Embodiment 14

[0113] A method for preparing sodium ion hard carbon by in-situ doping S-doped lignin-modified phenolic resin, comprising the following steps:

[0114] (1) First, 5 g of sodium lignin sulfonate and 6.125 g of anhydrous sodium sulfite were dissolved in 30 mL of 3 mol / L NaOH aqueous solution, stirred for 1 h, and transferred to a high-pressure reactor at 160 ° C for reaction for 6 h to prepare a sulfonated lignin mixed solution;

[0115] (2) separating, washing, drying and grinding the sulfonated lignin mixed solution obtained in step (1) to obtain sulfonated lignin powder;

[0116] (3) Take 5 g of the sulfonated lignin powder obtained in step (2), first oxidize it, then condense it with a phenolic resin prepolymer to prepare a sulfonated lignin-modified phenolic resin, and finally carbonize and refine it at high temperature to obtain a sulfonated lignin-modified phenolic resin hard carbon.

[0117] The molecular structure properties and battery performance of the samples prepared in the above-mentioned Example 3, Examples 11 to 14 and Comparative Examples were tested, and the test results are shown in Table 3 below.

[0118] Table 3 Comparison of sodium storage performance of sulfonated lignin modified phenolic resin hard carbon with different reaction times in Example 3, Examples 11 to 14 and Comparative Examples

[0119]

[0120] From the comparison of the data in the above table, it can be seen that when the reaction time of sulfonated lignin is 4h, the discharge specific capacity is the highest.

[0121] In order to analyze the structure-activity relationship of OLPRC, its microstructure was analyzed by X-ray diffraction (XRD) spectroscopy. Figure 1 , Figure 2 and Figure 3 As shown, two obvious diffraction peaks were observed at about 23.60° and 43.10°, corresponding to the (002) crystal plane and the (100) crystal plane of the carbon material. The above samples were all prepared under the same pyrolysis conditions to obtain hard carbon, and there was no large shift in the position of the characteristic peaks. As the in-situ S-doped lignin sulfonation reaction proceeded, the diffraction peaks of the hard carbon obtained from the sulfonated lignin modified phenolic resin obtained under the optimal conditions (sodium sulfite addition amount 6.125g, 160°C, 4h) were relatively broad. This shows that the sulfonated lignin phenolic resin hard carbon prepared from the precursor synthesized under the optimal conditions has a better disordered structure. Some characteristic parameters of each hard carbon in the synthesis process are shown in Table 4 below. The interlayer spacing and carbon crystallite size and number of the sample were calculated by the Bragg equation and the Scherrer formula, respectively. Example 12 is the optimal sulfonated lignin phenolic resin hard carbon, and the calculation results show that its interlayer spacing (d 002 ) is the maximum Its carbon crystallite size (La) is relatively small and the number of crystallites is relatively the largest. Combined with the results of specific surface area, it can be seen that the in-situ doping of S element changes the molecular structure of lignin and affects the structure of the subsequent lignin resin. The sulfonated lignin phenolic resin with a special structure increases the interlayer spacing of hard carbon during pyrolysis due to the doping of S, and changes the size and number of carbon crystallites, and this change does not increase the specific surface area of ​​the hard carbon material. This phenomenon may be that the measure of doping S element, in the process of increasing the interlayer spacing, also synergizes with other functional groups in the sulfonated lignin phenolic resin, promotes the shrinkage of the pore structure, so that the hard carbon has a certain number of ultra-micropores or closed-pore structures, thereby improving the sodium storage performance of sodium-ion batteries.

[0122] Table 4 d peak data in XRD spectrum

[0123]

[0124] The sodium storage performance of the unsulfonated oxidized lignin resin hard carbon of the comparative example and the sulfonated lignin phenolic resin hard carbon obtained in Examples 1-14 was tested (Table 1-3). It can be seen that with the optimization of the sulfonation reaction of the in-situ doping of S in lignin, the reversible capacity and first efficiency of the sulfonated lignin phenolic resin hard carbon gradually increased, and the micropore volume of the obtained phenolic resin-based hard carbon increased while the sodium storage performance was stable and excellent. Among these phenolic resin-based hard carbon materials, the hard carbon prepared under the optimal conditions (sodium sulfite addition amount 6.125g, 160℃, 4h) has a sodium storage capacity of 0.05A g -1 The highest reversible capacity is 400 mAh g -1The initial Coulomb efficiency is about 81%. The above method reduces the raw material cost of phenolic resin-based hard carbon materials to a certain extent, improves the sodium storage performance of biomass-based resins, and provides a new way for the industrial application of biomass-based phenolic resin hard carbon.

[0125] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing sodium ion hard carbon by in-situ doping S-doped lignin-modified phenolic resin, characterized in that: First, sodium lignin sulfonate and anhydrous sodium sulfite are hydrothermally prepared to obtain sulfonated lignin, and then the sulfonated lignin is oxidized and polycondensed with a phenolic resin prepolymer to obtain a sulfonated lignin phenolic resin; the sulfonated lignin phenolic resin is then cured and carbonized to obtain a sulfonated lignin modified phenolic resin-based hard carbon.

2. The method for preparing sodium ion hard carbon by in-situ doped S-lignin modified phenolic resin according to claim 1, characterized in that: The mass ratio of the sodium lignin sulfonate to anhydrous sodium sulfite is 1:2 to 2:

1.

3. The method for preparing sodium ion hard carbon by in-situ doped S-lignin modified phenolic resin according to claim 2, characterized in that: The mass ratio of the sodium lignin sulfonate to anhydrous sodium sulfite is 1:1.

225.

4. The method for preparing sodium ion hard carbon by in-situ doped S-lignin modified phenolic resin according to claim 1, characterized in that: The preparation method of sulfonated lignin is as follows: sodium lignin sulfonate and anhydrous sodium sulfite are dissolved in a NaOH aqueous solution, stirred for 1 hour, and then heated for reaction to prepare sulfonated lignin. After separation, water washing, drying, and grinding, sulfonated lignin powder is obtained.

5. The method for preparing sodium ion hard carbon by in-situ doped S-lignin modified phenolic resin according to claim 4, characterized in that: The temperature of the heating reaction is 100-200°C.

6. The method for preparing sodium ion hard carbon by in-situ doped S-lignin modified phenolic resin according to claim 5, characterized in that: The temperature of the heating reaction was 160°C.

7. The method for preparing sodium ion hard carbon by in-situ doped S-lignin modified phenolic resin according to claim 4, characterized in that: The heating reaction time is 2-6h.

8. The method for preparing sodium ion hard carbon by in-situ doped S-lignin modified phenolic resin according to claim 7, characterized in that: The heating reaction time is 4 h.

9. A sulfonated lignin phenolic resin-based hard carbon prepared by the method according to any one of claims 1 to 8.

10. Use of the sulfonated lignin phenolic resin-based hard carbon according to claim 9 in a negative electrode material for sodium ion batteries.

Citation Information

Patent Citations

  • Highly-sulfonated lignosulfonate water reducer and preparation method thereof

    CN107010866A

  • Preparation method of lignin-type negative electrode composite additive used for low-temperature-resistant lead carbon battery

    CN107611442A

  • Lignin-based phenolic resin and preparation method thereof

    CN117069901A

  • Lignin-based sulfur-doped activated carbon for supercapacitor electrode material and preparation method and application of lignin-based sulfur-doped activated carbon

    CN117524743A

  • Molecular-weight-controllable oxidized lignin modified phenolic resin-based hard carbon as well as preparation method and application thereof

    CN117963877A